Public order policing: use of force - Fomby, Spencer (Public Order Policing, 2024)
Public order policing is one of the most complex areas of modern policing and requires specialized training and expertise. When police intervene in a protest event, the focus is often on the use of force. While police in other Western countries have invested considerable resources in improving public order policing, American police agencies have long neglected this specialty. By summarizing historical trends and current challenges, this chapter will provide an overview of the current use of force landscape in American public order policing. Through case studies and real-world examples, this chapter will also provide guidance for police leaders to develop effective use-of-force capabilities that conform with best practices, legal restrictions, and model policies.